New Lexicon Adaptation in the Development of Creative Tourism - Luh Eka Susanti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
This article describes a number of new language terms in their development in the world of creative tourism, especially for tourists. This term arose as a result of the growing and varied types of new tourism that emerged because of the need to relieve boredom from the fatigue of daily routines. In addition, the use of this term is also inseparable from the development and proliferation of the use of social media among the global community. Even these terms are increasingly embedded in the minds of tourists and the surrounding community so that all elements of creative tourism are now commonplace in using this language variation which is very influenced with the changing needs of tourists. Generally, this language term is a combination of two words that refer to new meanings in the needs of contemporary creative tourism. Keywords: language terms, creative tourism, social media